2017
DOI: 10.3389/fimmu.2017.00486
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Study of CD83 Reveals an Upregulation and Higher Production of sCD83 in Lymphocytes from Pregnant Mice

Abstract: For the normal development of pregnancy, a balance between immune tolerance and defense is crucial. However, the mechanisms mediating such a balance are not fully understood. CD83 is a transmembrane protein whose expression has been linked to anti-inflammatory functions of T and B cells. The soluble form of CD83, released by cleavage of the membrane-bound protein, has strong anti-inflammatory properties and was successfully tested in different mouse models. It is assumed that this molecule contributes to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 80 publications
2
10
0
Order By: Relevance
“…Moreover, patients with AR showed significantly reduced sCD83 serum levels, which were inversely correlated with IgE-levels (70). Since B cells are presumably the major source of naturally occurring sCD83 (16,71), these new data perfectly fit the Th2-skewed immunity observed in mice with CD83-deficient B cells (47).…”
Section: Cd83 Binding Partners and Signaling Cascadessupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, patients with AR showed significantly reduced sCD83 serum levels, which were inversely correlated with IgE-levels (70). Since B cells are presumably the major source of naturally occurring sCD83 (16,71), these new data perfectly fit the Th2-skewed immunity observed in mice with CD83-deficient B cells (47).…”
Section: Cd83 Binding Partners and Signaling Cascadessupporting
confidence: 69%
“…Apart from this, IDO activity, also likely induced by CD83, has been shown to be essential for fetal tolerance (119,122). In this respect, a striking recent murine study revealed that B and T lymphocytes, but not DCs, upregulate CD83 expression at day 14 of pregnancy (71). Moreover, the sexual hormone progesterone induces CD83 expression in murine T and B cells, but also in DCs in vitro.…”
Section: Pregnancymentioning
confidence: 99%
“…This member of the Ig superfamily is expressed primarily on activated leukocytes, including DCs and regulatory T cells (Tregs), as well as on thymic epithelial cells (TECs) (6)(7)(8)(9). A soluble form of CD83 (sCD83), comprising the extracellular domain, was detected at low levels in sera of healthy individuals and in increased concentrations in patients with hematological malignancies (10)(11)(12), and reports suggested B cells as a major source of naturally occurring sCD83 (13). Several studies demonstrated profound immunomodulatory effects of sCD83 in different animal models of autoimmune diseases and transplantation (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell suspensions from para-aortic lymph nodes, inguinal lymph nodes, and thymus were obtained as previously described (Packhäuser et al 2017). The tissue was carefully pressed through a 40-µm nylon cell strainer and washed with PBS.…”
Section: Cell Preparationmentioning
confidence: 99%
“…Recently, we suggested that the soluble form of the transmembrane molecule CD83 (sCD83) could represent an important factor contributing to pregnancy maintenance (Packhäuser et al 2017). Anti-inflammatory properties of sCD83 have been extensively examined in mouse models of autoimmunity, allograft transplantation and inflammatory disease (Lan et al 2010, Bock et al 2013, Starke et al 2013, Eckhardt et al 2014, Lin et al 2018.…”
Section: Introductionmentioning
confidence: 99%